2014
DOI: 10.1590/s1517-70762014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of particleboard bamboo waste bonded with urea formaldehyde and castor oil based adhesive

Abstract: This study evaluated the physical and mechanical characteristics of particleboards made of bamboo waste from the species Dendrocalamus giganteus bonded with two different types of adhesives: urea-formaldehyde (UF) and a castor oil based adhesive (M). Thus, eight types of particleboards were produced in the proportions of 6%, 8%, 10% and 12% for each adhesive. The results showed that particleboards produced with UF and M adhesives had acceptable behavior for physical tests according to the Brazilian standard NB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 10 publications
0
20
0
8
Order By: Relevance
“…Several studies on the experimental manufacture and particleboard quality using different bamboo species and wood particles, isolated or mixed, have been carried out; for example, those conducted by Vital & Haselein (1988), Calegari et al (2007), Arruda et al (2011), Morais (2011), Melo et al (2014, Valarelli et al (2014), Morais et al (2015), Nurhazwani et al (2016). Among these studies, only that carried out by Nurhazwani et al (2016) used Dendrocalumus asper bamboo, and none of them addressed the influence of particle size on panel properties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the experimental manufacture and particleboard quality using different bamboo species and wood particles, isolated or mixed, have been carried out; for example, those conducted by Vital & Haselein (1988), Calegari et al (2007), Arruda et al (2011), Morais (2011), Melo et al (2014, Valarelli et al (2014), Morais et al (2015), Nurhazwani et al (2016). Among these studies, only that carried out by Nurhazwani et al (2016) used Dendrocalumus asper bamboo, and none of them addressed the influence of particle size on panel properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nascimento et al reported that the values of WA for medium density of the particle boards which employed from Eucalyptus and Pinus had an average value between 12% and 16% for water absorption in 2 hours [19]. Valarelli et al [20] also reported the similar results for the particleboards from bamboo and castor oil based adhesive.The effect of particle size of material on the water absorption is not significant. However, from both results (WA and TS), it shows the ability of particleboards to produce the lower percentage of WA was increased as the ratio of resin was reduced.…”
Section: Fig 5 Water Absorptionmentioning
confidence: 76%
“…Although there are no competitive engineered bamboo industries in Brazil, a high local potential, regarding the bamboo plantation and commercialization, makes reasonable to perform scientific research related to the development of high value-added products using bamboo. In fact, several studies have been made in Brazil using agricultural waste for the particleboard production (Calegari et al 2007, Fiorelli et al 2012a, Fiorelli et al 2012b, Fiorelli et al 2014, Belini et al 2014, Valarelli et al 2014, Zaia et al 2015. Qisheng et al (2001) classified bamboo panels according to their material composition and product structure: bamboo-plywood products, laminated products (laminated bamboo from strips), chipboard products (bamboo chip/particleboard) and composite board products.…”
Section: Bamboo Particleboardsmentioning
confidence: 99%
“…The resin normally consists of an organic adhesive: urea formaldehyde, phenol formaldehyde, castor oil-based polyurethane resin, polyvinyl acetate (PVA) and others. The following processes are normally performed for the production of bamboo particleboards: the obtained bamboo chips/particles are dried, mixed with resin, pre-formed and hot-pressed in the form of panels (Valarelli et al 2014).…”
Section: Bamboo Particleboardsmentioning
confidence: 99%